(3CfS GdCHQGQ hWQGFb GdCNjGQs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s ((3YeQ Hf YKeGf Hf YeQ GdYLej s)
(3ChdgG (B:s
(3hjLO faYg jhe dGjfaY eGd hdG Hfhf EdG ef CJi Gddg HbdH Sdje dbhdg Udi Gddg Ydjg hSde ef Sf SfI MSfI adg CLQgG hCLQ ef Yed HgG Edi jhe GdbjGeI s
(3BNQgG (B:s
(3hJTJgj dfG GdPj dGoHO dj ef dbGFg EPG UM LSej cGO jZdHfj Gdghi Je GdcJGH HMeO Gddg s
(3GdfSNI HgG MhGTs
(3QJHg Ydi NeSjf eLdSkGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
Keywords: (3GdJUha hGdBOGH GdTQYjIs